Controlled Parallel Crystallization of Lithium Disilicate and Diopside Using a Combination of Internal and Surface Nucleation - Rampf, Markus; Dittmer, Marc; Ritzberger, Christian; Höland, Wolfram (Frontiers in Materials, 2016)
In the mid-twentieth century, Dr. Donald Stookey identified the importance and usability of nucleating agents and mechanisms for the development of glass-ceramic materials. Today, a number of various internal and surface mechanisms as well as combinations thereof have been established in the production of glass-ceramic materials. In order to create new innovative material properties, the present study focuses on the precipitation of CaMgSi2O6 as a minor phase in Li2Si2O5-based glass-ceramics. In the base glass of the SiO2–Li2O–P2O5–Al2O3–K2O–MgO–CaO system, P2O5 serves as nucleating agent for the internal precipitation of Li2Si2O5 crystals, while a mechanical activation of the glass surface by means of ball milling is necessary to nucleate the minor CaMgSi2O6 crystal phase. For a successful precipitation of CaMgSi2O6, a minimum concentration of MgO and CaO in the range between 1.4 and 2.9 mol% in the base glasses was determined. The nucleation and crystallization of both crystal phases takes place during sintering a powder compact. Dependent on the quality of the sintering process, the dense Li2Si2O5–CaMgSi2O6 glass-ceramics show a mean biaxial strength of up to 392 ± 98 MPa. The microstructure of the glass-ceramics is formed by large (5–10 μm) bar-like CaMgSi2O6 crystals randomly embedded in a matrix of small (≤1 μm) plate-like Li2Si2O5 crystals arranged in an interlocking manner. While there is no significant influence of the minor CaMgSi2O6 phase on the strength of the material, the translucency of the material decreases upon precipitation of the minor phase.